Marine Microbiology : Ecology and Applications - Munn, C. B (BIOS Scientific Publishers, 2004)
"The Advanced Text series is designed for students taking advanced-level courses in the life sciences, including final year undergraduates and taught MSc. Titles in this series will also be invaluable to researchers new to a field and to established researchers as a basic reference."--Jacket.